Avaliação da saturação venosa de oxigênio femoral como substituta da saturação venosa central em pacientes graves - Marti, Yara Nishiyama [UNIFESP] (2016)
One of the factors that limits perfusion assessment in critically ill patients is catheterization of the femoral vein instead of the subclavian or internal jugular vein The purpose of this study was to test if venous blood draw from femoral access could be used to estimate the central venous oxygen saturation (ScvO2) and arterial lactate levels (LacA) in critically ill patients. In this prospective, observational study, we included patients over 18 years of age who were admitted to the intensive care unit with both femoral venous and central venous catheters; written informed consent was obtained from all participants. We excluded pregnant women and patients with a functioning arteriovenous fistula, amputated limbs, venous thrombosis, or barbiturate coma as well as those who were previously included in the study. Blood samples were simultaneously collected from arterial catheter and distal ports of the central and femoral catheters. The Bland-Altman analysis and Spearman correlation were used to compare the femoral venous saturation (SfvO2) and ScvO2 as well as the LacA and femoral lactate (LacF). A pre-specified subgroup analysis was conducted in patients with signs of hypoperfusion. In addition, the clinical agreement was also investigated. From April 2011 to November 2012, blood samples were obtained in 26 patients. In 107 paired samples, there was a moderate correlation (r = 0.686, p < 0.0001) between the ScvO2 and SfvO2 and a bias of 8.24 ± 10.44 (95% limits of agreement (LOAs) of -12.23 to 28.70) in the Bland-Altman analysis. In 102 paired samples, there was a strong correlation between the LacA and LacF levels (r = 0.972, p < 0.001) and a bias of -2.71 ± 9.86 (95% LOA of -22.03 to 16.61). The presence of hypoperfusion did not significantly change these results. The clinical agreement between the ScvO2 and SfvO2 was inadequate, since there were different therapeutic decisions in 22.4% of the situations. For the lactate analysis, there were similar therapeutic decisions in 94.8% of the cases. In conclusion, the SfvO2 should not be used as surrogate of the ScvO2. However, the strong correlation and satisfactory clinical agreement between the LacF and LacA levels allows for the use of the LacF level in clinical practice, albeit with caution because the limits of agreement were wide.